Biomekanika Olahraga untuk Pengurangan Risiko Cedera dan Peningkatan Performa Olahraga - Prasetyowibowo, Ari; Nasrullo, Ahmad; -, Widiyanto (Smart Sport, 2022)
All life structures on the planet, including people, are continually exposed to the widespread power of attractive energy, and subsequently to powers from the inside and encompassing the body. Through the investigation of the cooperation of these powers and their belongings, the structure, capacity and movement of our bodies can be analyzed and the subsequent information applied to advance personal satisfaction. Under gravity and different loads, and constrained by the sensory system, human development is accomplished through a complex and profoundly planned mechanical communication between bones, muscles, tendons and joints inside the outer muscle framework. Any injury to, or sore in, any of the singular components of the outer muscle framework will change the mechanical collaboration and cause corruption, precariousness or handicap of development. Then again, legitimate adjustment, control and control of the mechanical climate can assist with forestalling injury, right anomaly, and speed recuperating and recovery. In this manner, understanding the biomechanics and stacking of every component during development utilizing movement examination is useful for concentrating on sickness etiology, settling on conclusions about therapy, and assessing therapy impacts. In this article, the set of experiences and technique of human development biomechanics, and the hypothetical and exploratory strategies produced for the investigation of human development, are assessed. Instances of movement examination of different patient gatherings, prostheses and orthoses, and sports and activities, are utilized to exhibit the utilization of biomechanical and stereophotogrammetry-based human movement investigation studies to resolve clinical issues. It is recommended that further investigation of the biomechanics of human development and its clinical applications will profit from the combination of existing designing procedures and the proceeding with advancement of new innovation. Keywords: Biomechanics, Human motion, Analysis, Sports